Enhancing waste bank managers’ capacity through administrative management training - Sukapti Sukapti; Purwaningsih Purwaningsih; Agustin Nurmanina (University of Merdeka Malang, 2024)
The establishment of waste bank units is one of the solutions to address the waste management issues in Samarinda City. However, waste bank managers often lack the necessary knowledge and capacity to effectively manage these units, resulting in limited development. This community service activity, in the form of training, aims to enhance the managerial knowledge and skills of waste bank managers, focusing on waste sorting, operational techniques, and administrative management. Managerial capacity is crucial for the sustainability of waste bank activities. The participants of this activity were the managers and cadres of the Turi Putih RT 48 waste bank unit in Sempaja Timur. The training was conducted by the director of the main waste bank, who has practical experience in waste bank management. The training employed lectures, brainstorming sessions, practical exercises, and mentoring. It was conducted over two days, followed by two months of mentoring. This activity successfully improved the managers’ capacity in three areas: knowledge of valuable waste types, skills in waste sorting to increase the selling value of waste, and skills and practices in orderly administration.